Evaluation of antioxidant potential of organic vegetables during cold storage - Santos, Maria Letícia de Almeida Kasctin dos; Gonzales, Juliana; Vicenzi, Raul (Revista de Administração da UFSM, 2020)
The relation between an antioxidant-rich diet with protection against some diseases such as Alzheimer’s and cardiovascular diseases has increased research on the evaluation of these components in food. Another factor related to some diseases is the consumption of food produced from conventional agriculture with the excessive use of agrochemicals and the search for food free of pesticides increases the demand for products grown in organic systems. Aiming to relate these two themes, the present study aimed to produce a kit of organic vegetables and evaluate antioxidant activity during storage at reduced temperatures. The results indicate a sudden drop in antioxidant activity and phenolic compound concentration in the first month of storage.